(untitled) (Research, Society and Development, 2022)
Objective: To apprehend the maternal representations regarding music therapy and breastfeeding of premature children. Method: This is a qualitative study, based on the Theory of Social Representations. The study setting was the Intermediate Care Unit of a university hospital in northern Paraná. The collection took place from July to August 2021, mothers of newborns with a gestational age of less than 34 weeks, and who were breastfeeding in the first seven days of life, participated in this study. Data were analyzed using the methodological framework of the Collective Subject Discourse. Results: From the analysis of the speeches of the 15 participating mothers, three central ideas emerged:): CI1) Breastfeeding is giving life, CI2) Escaping reality through music and CI3) Music interfering with communication with the child. Conclusion of the study: Music therapy can bring benefits to the breastfeeding of premature babies, however, the help of a trained professional is needed for this intervention, thus avoiding iatrogenic events.